Salsalate reduces atherosclerosis through AMPKβ1 in mice - Emily A. Day; Rebecca J. Ford; Brennan K. Smith; Vanessa P. Houde; Stephanie Stypa; Sonia Rehal; Sarka Lhotak; Bruce E. Kemp; Bernardo L. Trigatti; Geoff H. Werstuck; Richard C. Austin; Morgan D. Fullerton; et al. (Elsevier, 2021)
Objective: Salsalate is a prodrug of salicylate that lowers blood glucose in people with type 2 diabetes. AMP-activated protein kinase (AMPK) is an αβγ heterotrimer which inhibits macrophage inflammation and the synthesis of fatty acids and cholesterol in the liver through phosphorylation of acetyl-CoA carboxylase (ACC) and HMG-CoA reductase (HMGCR), respectively. Salicylate binds to and activates AMPKβ1-containing heterotrimers that are highly expressed in both macrophages and liver, but the potential importance of AMPK and ability of salsalate to reduce atherosclerosis have not been evaluated. Methods: ApoE−/− and LDLr−/− mice with or without (−/−) germline or bone marrow AMPKβ1, respectively, were treated with salsalate, and atherosclerotic plaque size was evaluated in serial sections of the aortic root. Studies examining the effects of salicylate on markers of inflammation, fatty acid and cholesterol synthesis and proliferation were conducted in bone marrow-derived macrophages (BMDMs) from wild-type mice or mice lacking AMPKβ1 or the key AMPK-inhibitory phosphorylation sites on ACC (ACC knock-in (KI)-ACC KI) or HMGCR (HMGCR-KI). Results: Salsalate reduced atherosclerotic plaques in the aortic roots of ApoE−/− mice, but not ApoE−/− AMPKβ1−/− mice. Similarly, salsalate reduced atherosclerosis in LDLr−/− mice receiving wild-type but not AMPKβ1−/− bone marrow. Reductions in atherosclerosis by salsalate were associated with reduced macrophage proliferation, reduced plaque lipid content and reduced serum cholesterol. In BMDMs, this suppression of proliferation by salicylate required phosphorylation of HMGCR and the suppression of cholesterol synthesis. Conclusions: These data indicate that salsalate suppresses macrophage proliferation and atherosclerosis through an AMPKβ1-dependent pathway, which may involve HMGCR phosphorylation and cholesterol synthesis. Since rapidly-proliferating macrophages are a hallmark of atherosclerosis, these data indicate further evaluation of salsalate as a potential therapeutic agent for treating atherosclerotic cardiovascular disease.